Atmospheric Concentrations of New Persistent Organic Pollutants and Emerging Chemicals of Concern in the Group of Latin America and Caribbean (GRULAC) Region - Rauert, Cassandra; Harner, Tom; Schuster, Jasmin K; Eng, Anita; Fillmann, Gilberto; Castillo, Luisa Eugenia; Fentanes, Oscar; Villa Ibarra, Martín; Miglioranza, Karina S B; Moreno Rivadeneira, Isabel; Pozo, Karla; Aristizábal Zuluaga, Beatriz Helena (Environmental science & technology, 2018)
A special initiative was run by the Global Atmospheric Passive Sampling (GAPS) Network to provide atmospheric data on a range of emerging chemicals of concern and candidate and new persistent organic pollutants in the Group of Latin America and Caribbean (GRULAC) region. Regional-scale data for a range of flame retardants (FRs) including polybrominated diphenyl ethers (PBDEs), organophosphate esters (OPEs), and a range of alternative FRs (novel FRs) are reported over 2 years of sampling with low detection frequencies of the novel FRs. Atmospheric concentrations of the OPEs were an order of magnitude higher than all other FRs, with similar profiles at all sites. Regional-scale background concentrations of the poly- and perfluoroalkyl substances (PFAS), including the neutral PFAS (n-PFAS) and perfluoroalkyl acids (PFAAs), and the volatile methyl siloxanes (VMS) are also reported. Ethyl perfluorooctane sulfonamide (EtFOSA) was detected at highly elevated concentrations in Brazil and Colombia, in line with the use of the pesticide sulfluramid in this region. Similar concentrations of the perfluoroalkyl sulfonates (PFAS) were detected throughout the GRULAC region regardless of location type, and the VMS concentrations in air increased with the population density of sampling locations. This is the first report of atmospheric concentrations of the PFAAs and VMS from this region.
Keywords: Flame Retardants; Colombia; Halogenated Diphenyl Ethers; karibský region; Brazil; Latin America; látky znečišťující životní prostředí; Environmental Monitoring; monitorování životního prostředí; Latinská Amerika; Brazílie; Environmental Pollutants; Kolumbie; retardanty hoření; Caribbean Region; halogenované difenylethery